Black Feminism, Class, and Racism in Audre Lorde’s Poems and Essays - Correia de Sousa, Levi; Itikawa Tanaka, Elder Koei (Cadernos de Gênero e Diversidade, 2025)
This article intends to analyze the poem Power”, from “The Collected Poems of Audre Lorde” using Lorde’s “Sister Outsider” essays and other authors such as bell hooks and Angela Davis as support to reflect and discuss racism, Black feminism, and class. We aim to understand the process of silencing Black women within feminism in the USA in the 1960s, recognizing the importance of poetry as a revolutionary tool, enabling Black women to speak for themselves.